Monetary costs and hospital burden associated with the management of invasive fungal infections in Mexico: a multicenter study - Corzo León, Dora Edith; Perales Martínez, Diana; Martin Onraet, Alexandra; Rivera Martínez, Norma; Camacho Ortiz, Adrián; Villanueva Lozano, Hiram (Elsevier, 2018)
Background: Invasive fungal infections (IFIs) affect >1.5 million people per year. Nevertheless, IFIs are usually neglected and underdiagnosed. IFIs should be considered as a public-health problem and major actions should be taken to tackle them and their associated costs. Aim To report the incidence of IFIs in four Mexican hospitals, to describe the economic cost associated with IFIs therapy and the impact of adverse events such as acute kidney injury (AKI), liver damage (LD), and ICU stay. Methods: This was a retrospective, transversal study carried-out in four Mexican hospitals. All IFIs occurring during 2016 were included. Incidence rates and estimation of antifungal therapy's expenditure for one year were calculated. Adjustments for costs of AKI were done. An analysis of factors associated with death, AKI, and LD was performed. Results: Two-hundred thirty-eight cases were included. Among all cases, AKI was diagnosed in 16%, LD in 25%, 35% required ICU stay, with a 23% overall mortality rate. AKI and LD showed higher mortality rates (39% vs 9% and 44% vs 18%, respectively, p < 0.0001). The overall incidence of IFIs was 4.8 cases (95% CI = 0.72–8.92) per 1000 discharges and 0.7 cases (95% CI = 0.03–1.16) per 1000 patients-days. Invasive candidiasis showed the highest incidence rate (1.93 per 1000 discharges, 95% CI = −1.01 to 2.84), followed by endemic IFIs (1.53 per 1000 discharges 95% CI = −3.36 to 6.4) and IA (1.25 per 1000 discharges, 95% CI = −0.90 to 3.45). AKI increased the cost of antifungal therapy 4.3-fold. The total expenditure in antifungal therapy for all IFIs, adjusting for AKI, was $233,435,536 USD (95% CI $6,224,993 to $773,810,330). Conclusions: IFIs are as frequent as HIV asymptomatic infection and tuberculosis. Costs estimations allow to assess cost-avoidance strategies to increase targeted driven therapy and decrease adverse events and their costs.